penelitian tindakan kelas MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PERKALIAN DI KELAS 2 MELALUI PEMBELAJARAN BERBASIS PERMAINAN PADA UPT SD N 064974 MEDAN: upaya meningkatkan kopetensi dasar perkalian melalui metode inovatif dan interaktif - Handa Yenni Hotma Siregar, Yusni Khairul Amri, Amelia Mayasari (STKIP Subang, 2025)
This study aims to improve the learning outcomes of grade 2 students of UPT SDN 064974 Medan on multiplication material through game-based learning. This method is expected to increase student involvement, facilitate understanding of multiplication concepts, and improve their learning outcomes with three cycles involving 23 students. In the pre-cycle stage, mathematics learning outcomes showed an average score of 46 with a completion rate of 25%. In cycle I, there was an increase in the average score to 58, with a completion rate reaching 35%. After the implementation of cycle II, there was an increase in the average score to 64, with a completion rate reaching 47%. There was a significant increase after the implementation of cycle III, with an average score reaching 88 and a completion rate of 90%. These results indicate that using game-based learning with multiplication smart board media effectively improves the mathematics learning outcomes of grade 2 students at UPT SD N 064974 Medan